Analisis Cost-Volume-Profit untuk Perencanaan Laba pada UD. Budi Luhur Demak - Erawati Kartika; Puji Setya Sunarka (STIE Widya Manggala, 2019)
Profit is one indicator in evaluating the performance of a company. To achieve the required profit, good profit planning is needed. Because with the existence of better profit planning, the company in controlling costs will be more directed. Cost-volume-profit analysis (cost-volume-profit) is a very necessary compilation of companies wanting to do profit planning and decision making related to the relationship between costs, sales volume and prices. The purpose of this study was to study how cost-volume-profit in 2015-2016 can be used for income in 2016 at UD. Budi Luhur Demak. The method used was descriptive method. The results of this study indicated that cost-volume-profit analysis from 2015-2016 at UD. Budi Luhur increased profits while sales volume decreased and fixed costs increased. Through this cost-volume-profit analysis, it can be predicted the minimum number of sales that must be achieved to obtain agreed profits in 2016. It is better if company management can apply cost-volume-profit analysis in the profitability.